Optimización De La Red De Acueducto Y Diseño Integral Deun Sistema De Ariete Hidráulico En La Vereda San Juan, Municipio De Popayán (2024)
The research aims to optimize the aqueduct network and design a hydraulic ram system in the San Juan area of Popayán, in order to improve access to drinking water for its 571 inhabitants. To achieve this, data was collected on the existing infrastructure, followed by a hydraulic analysis and modeling of the aqueduct network, as well as an evaluation of the flow rate and required pressures.